Protective Effect of Ethanolic Extract of Tabernaemontana divaricata (L.) R. Br. against DEN and Fe NTA Induced Liver Necrosis in Wistar Albino Rats - Poornima, Kannappan (Hindawi Publishing Corporation, 2014)
This study is an attempt to evaluate the hepatoprotective activity of Tabernaemontana divaricata against DEN and Fe NTA induced liver necrosis in rats. Ethanolic extract of the whole plant of Tabernaemontana divaricata at doses of 200 and 400 mg/kg body weight and 5-fluorouracil (standard drug) was orally administered to male Wistar Albino rats once daily for 24 weeks, simultaneously treated with the carcinogen DEN and Fe NTA. In simultaneously treated animals, the plant extract significantly decreased the levels of uric acid, bilirubin, AST, ALT, and ALP in serum and increased the levels of liver marker enzymes in liver. Treatment with the extracts resulted in a significant increase in the levels of antioxidants accompanied by a marked reduction in the levels of malondialdehyde when compared to DEN and Fe NTA treated group. When compared with 200 mg/kg bw rats, 400 mg/kg bw rats and 5-fluorouracil treated rats showed better results in all the parameters. The histopathological studies confirmed the protective effects of extract against DEN and Fe NTA induced liver necrosis. Thus, it could be concluded that the use of Tabernaemontana divaricata extract in the treatment of carcinogen induced hepatic necrosis.